3-5x=1-6x

Simple and best practice solution for 3-5x=1-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-5x=1-6x equation:


Simplifying
3 + -5x = 1 + -6x

Solving
3 + -5x = 1 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
3 + -5x + 6x = 1 + -6x + 6x

Combine like terms: -5x + 6x = 1x
3 + 1x = 1 + -6x + 6x

Combine like terms: -6x + 6x = 0
3 + 1x = 1 + 0
3 + 1x = 1

Add '-3' to each side of the equation.
3 + -3 + 1x = 1 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = 1 + -3
1x = 1 + -3

Combine like terms: 1 + -3 = -2
1x = -2

Divide each side by '1'.
x = -2

Simplifying
x = -2

See similar equations:

| -6y-2=5y-3 | | 3(2x-4)=3x-33 | | x+x+0.56x=28.6 | | 3(2)(-4)=0 | | -3(x+3)+3=-6 | | 2c-5=2c+5 | | 720-3=7X | | 3(4x+8)=-31+43 | | 8(x+2)+6=22 | | 225000x+x=600000000 | | 6(x+7)-26=6x | | Ax-5b=2c | | X-3/3=2x-1/4 | | y/2.53=-5 | | 2x-9=-3x+36 | | -7p-(4-9p)=-10+25p/4 | | 5b+7+7=7+6b | | X^2=.035 | | -72XY^2+45X^2Y= | | 2,1/2x=10 | | 13-(x+7)=7x-2 | | (3a^3+a-5)-(6-5a^3-2a^2)= | | 2(4+5x)+10=(-5x+12) | | 3-27x/4=-x/2-1/4(-3x-4) | | 14x=-7+21 | | 17=4(9-2)+29 | | -3+5x=2x+6 | | -8/9-2/3 | | -4x+y=-10 | | h/9=8 | | 3x+3/2=24 | | X-4=-(3x-3)+5 |

Equations solver categories